The application of UHPC on the monolithic part of the Štvanice footbridge - Davidová, Vendula; David, Tomáš; Reiterman, Pavel; Šmilauer, Vít (Acta Polytechnica CTU proceedings, 2024)
The use of UHPC with fibers is becoming an increasingly common topic in the world. This material is used for its superior mechanical and physical properties and long service life. However, the production cost is high, hence UHPC is used for special applications or for smaller prefabricated parts. This paper focuses on UHPC application for the construction of the Štvanice Footbridge, Prague, the Czech Republic. A monolithic part of the structure was made of UHPC from fresh transport concrete, which was produced by Skanska Transbeton. The special feature is that about 126m3 of fresh concrete was industrially prepared. This concrete achieved the properties of SCC and the final 28 day compressive strength was 120MPa with tensile strength of 18.6 MPa. Due to high hydration heat release rate, an internal water cooling system was designed and sucessfully appled using water from Vltava River.